2009
DOI: 10.1007/s10750-009-9809-6
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of human influence during the last two centuries on two small oxbow lakes near Warsaw (Poland)

Abstract: Short sediment cores from two small oxbow lakes located in the Vistula valley near Warsaw (Poland) were analysed for chemical composition and zooplankton (Cladocera) remains. The results of these analyses were evaluated using ordination techniques and the results were used to reconstruct the history of human impact of the lakes. The cores were dated using the 210 Pb method. These analyses show that the collected sediments (60 cm-and 67 cm-long-cores) were deposited during the last 150-200 years. Cladocera asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Small oxbow lakes are especially sensitive to the local disturbances that are caused by human activity, primarily water management, land use changes and agriculture (GaLBarczyk-Gąsiorowska et al 2009). Oxbow lakes, located within agricultural areas, regulate the nutrient transfer towards rivers, mainly through the retention of matter.…”
Section: Concentration Of Nutrients and Water Conductivity In Oxbow Lmentioning
confidence: 99%
“…Small oxbow lakes are especially sensitive to the local disturbances that are caused by human activity, primarily water management, land use changes and agriculture (GaLBarczyk-Gąsiorowska et al 2009). Oxbow lakes, located within agricultural areas, regulate the nutrient transfer towards rivers, mainly through the retention of matter.…”
Section: Concentration Of Nutrients and Water Conductivity In Oxbow Lmentioning
confidence: 99%
“…Also correlations between Cladocera frequency and climatic conditions have been previously studied (Lotter et al, 1997;Szeroczyńska, 2006Kamenik et al, 2007. The initial interpretive possibilities for palaeoecological studies of Cladocera in flood records have been recently demonstrated, and tested mostly with young sediment (from the last two hundred years) associated with human activity (Galbarczyk-Gąsiorowska et al, 2009). To date there have not been many studies which present the use of Cladocera as a trace indicator of past flood events in oxbow lakes.…”
Section: Introductionmentioning
confidence: 99%
“…were recorded from shallow lakes and ponds in Hungary in macrophytes belts (Korponai et al, 2010a). Galbarczyk-Gąsiorowska et al (2009) found that remains of A. excisa, and K. latissima were associated with macrophyte occurrence in a lakebog transition zone in Stare Biele mire.…”
Section: Discussionmentioning
confidence: 98%
“…The low number of remains in this core section therefore can be explained by the slow recovery of the cladoceran community from sediment egg banks. In Cl-2 and Cl-3 zones (between 1950-1970) the co-occurrence of a high proportion of Bosmina longirostris and of phytophyllous cladoceran species indicates the development of a macrophyte bed with large open water patches due to a lentic water regime (Galbarczyk-Gąsiorowska et al, 2009). In Cl-4 zone, the absolute dominance of B. longirostris since 1970 is related to strong human impacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation